Assessment of liquid disposal originated by uranium enrichment at Aramar Experimental Center São Paulo-Brazil - Gerenutti, Marli; Goncalves, Marcos Moises; Rissato, Sandra Regina [UNESP]; de Oliveira, Jose Martins; dos Santos Reigota, Marco Antonio; Galhiane, Mario Sergio [UNESP] (Springer, 2012)
This work presents a liquid disposal monitoring originated from uranium enrichment process at Aramar Experimental Center from 1990 to 1998. Assessment of uranium, fluorides, ammoniacal nitrogen, chemical oxygen demand, and pH measurements were made in water samples and compared with results achieved in other countries, as North America and India. The liquid disposal evaluation, generated by uranium enrichment process, showed low levels, considering most parameters established by Federal and State Legislation, aiming environmental pollution control. However, uranium levels were above the limits established by Conselho Nacional do Meio Ambiente, Environment Protection Agency and mainly by the World Health Organization.
Keywords: Uranium; Environmental contamination; Water analysis